Motivasi Petani dalam Integrasi Sapi pada Kawasan Perkebunan Kelapa Sawit - Qohhaarudin Barokah Trisbyono; Novira Kusrini; Wanti Fitrianti (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2023)
This research holds significant importance in sustainable agricultural development in West Kalimantan, where the integration of cattle farming within oil palm plantations is an innovation that can impact farmers' economy, development, and social needs. The study was conducted in 2022, involving 130 respondents and employing both descriptive analysis and Structural Equation Modeling (SEM) methods. The analysis results reveal that farmers' motivation is influenced by internal and external factors such as experience, cosmopolitanism, external support, the availability of facilities, market guarantees, ease of integration, and perceived benefits from integration. This research provides a profound understanding of these dynamics, which can assist in designing more effective policies and strategies to promote and support the integration of cattle farming within oil palm plantations. Consequently, this research has the potential to significantly contribute to sustainable agricultural development and rural growth in Meliau District.